2011
DOI: 10.1007/s12686-011-9535-z
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms between two lines of European bison (Bison bonasus) detected by the use of Illumina Bovine 50 K BeadChip

Abstract: The population of European bison is divided into two lines: the Lowland-Bialowieza (LB) and the LowlandCaucasian (LC). Because of a very high level of inbreeding and the bottleneck effect, the use of routine sets of cattle microsatellite markers does not reveal significant differences between these genetic lines. Within the research we attempted to overcome this limitation by the use of a Single Nucleotide Polymorphisms panel (50 K Bovine BeadChip, Illumina). Genomic DNA was isolated from the blood of 10 Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 6 publications
0
14
2
1
Order By: Relevance
“…For comparison, in studies by Tokarska et al (2009) the 50 Lowland European bison (LB) tested gave a reading of 52,978 SNPs, of which 960 markers were polymorphic. In contrast, Kamiński et al (2012), despite testing only 10 European bison (five LB and five LC specimens), obtained 1,337 polymorphic SNPs. The number of markers was higher due to inclusion of both genetic lines in the studies and LC is intrinsically more diverse than LB, which is also noticeable in the present study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For comparison, in studies by Tokarska et al (2009) the 50 Lowland European bison (LB) tested gave a reading of 52,978 SNPs, of which 960 markers were polymorphic. In contrast, Kamiński et al (2012), despite testing only 10 European bison (five LB and five LC specimens), obtained 1,337 polymorphic SNPs. The number of markers was higher due to inclusion of both genetic lines in the studies and LC is intrinsically more diverse than LB, which is also noticeable in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…Oleński et al (2015) used for the first time the BovineHD microarray to find SNP markers associated with posthitis in the same genetic line. The first SNP analysis using the BovineSNP50 microarray which included both genetic lines (five individuals from LB and five individuals from LC) was performed by Kamiński et al in 2012. The aim of the present study was to identify a panel of SNP markers (among those assayed on the Illumina BovineSNP50 and BovineHD arrays) that could be used to analyse genetic structure, identify individuals and control the origin and relatedness of the European bison, as well as identify alleles specific to the two genetic lines: Lowland (LB) and Lowland-Caucasian (LC). This is the first study using BovineHD microarray to compare genetic structure of two genetic lines of European bison.…”
Section: Introductionmentioning
confidence: 99%
“…In a panel of a similarly large number of SNPs designed for cattle, only about 2.5 and 3% of the cross‐species amplifications were successful in two lines of European bison and two species of antelopes respectively (Kaminski et al . ; Ogden et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Performing GWAS in wild living species is usually difficult, as all the commercially available microarray sets are designed for model or domestic animals. It has been shown that cattle SNP microarrays work well in bison species [ 6 - 8 ]. The European Bison ( Bison bonasus ), (EB), after extinction in the wild before World War II, was restored based on progeny of just 12 individuals preserved in private collections and zoological gardens [ 9 ].…”
Section: Introductionmentioning
confidence: 99%